Pengaruh Kepemimpinan Instruksional Terhadap Prestasi Siswa: Pendekatan Manajemen Pendidikan yang Efektif - Supriatna, Eka; Elfridawati Mai Dhuhani; Ahyani, Edi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study investigates the practice of instructional leadership with qualitative methods with a descriptive approach to analysis. Involving principals, teachers, and teaching staff with a total of 15 respondents. The data collection method used is through observation, documentation and interviews. Data analysis techniques through data collection, data presentation and data verification. The results show that instructional leadership includes concrete steps in shaping an inclusive and proactive learning culture. These findings are in line with the literature emphasizing the positive role instructional leadership plays on teacher motivation and commitment. However, to evaluate its concrete impact on student achievement, further research is needed. The study recommends developing leadership training programs, strengthening teacher collaboration and participation, and developing supportive school policies. Periodic monitoring and evaluation is also proposed as an important step in ensuring the effective implementation of instructional leadership practices. Through the implementation of these recommendations, it is expected to continue to improve the quality of education and contribute to the development of the literature on instructional leadership